Model of The 21st Century Vocational Teacher Competency Development - Pakaja, Jemmy A.; Kamdi, Waras; Hadi, Syamsul; Yoto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The development of Information and Communication Technology (ICT) had changed our lives profoundly. The period known as the industrial revolution had forced various changes in all fields of knowledge. In facing the era of the industrial revolution 4.0, Human Resources development became an important factor. Human resources, mainly Vocational High Schools (Sekolah Menengah Kejuruan/SMK) graduates were one of the spearheads to fulfil the needs of the industrial worlds. To achieve this goal, it was necessary to improve the quality of education. Teachers, as one of the main components in the process of increasing the quality of human resources, were required to be professionals in their fields and possess competencies according to the needs of the times. In efforts to improve the quality of the education field, developing teacher competency is a top priority. The purpose of this study is to examine the theories and models of teacher competencies and their development, especially vocational teachers. This study used a literature review method. The initial study was conducted by examining and considering the results of previous research related to the competence of vocational teachers, then proceeded with the study of theories and models of teacher competencies and their development. The results of this literature review lead to a conceptual framework for the development of vocational teacher competencies. The conceptual framework offered can be used as a basis for reference and guidance for further studies conducted by researchers in the future.